Refined Temporal-to-Frontal Horn Shunt for Treatment of Trapped Temporal Horn After Surgery of Peri- or Intraventricular Tumor: A Case Series Study - Ren, Xiaohui; Cui, Yong; Yang, Chuanwei; Jiang, Zhongli; Lin, Song; Lin, Zhiqin (Frontiers in Oncology, 2021)
Background Trapped temporal horn (TTH) is a localized hydrocephalus that can be treated with cerebrospinal fluid diversion. Refined temporal-to-frontal horn shunt (RTFHS) through the parieto-occipital approach is rarely reported in the literature and its effectiveness remains unclear. The aim of the present study is to investigate the efficacy and outcome of RTFHS for treatment of TTH. Materials and Methods We consecutively enrolled 10 patients who underwent RTFHS for TTH after surgical resection of peri- or intraventricular tumors from February 2018 to March 2021. Clinical, radiological, and follow-up data were collected and analyzed. The most common underlying pathology was meningioma (n=4), followed by central neurocytoma (n=3), thalamic glioblastoma (n=2), and anaplastic ependymoma (n=1). Results The mean Karnofsky performance scale (KPS) score and TTH volume at onset were 54.0 ± 15.1 (range 40-80) and 71.3 ± 33.2cm3 (range 31.7-118.6cm3), respectively. All patients (10/10, 100.0%) presented with periventricular brain edema (PVBE), while midline shift was observed in 9 patients (9/10, 90.0%). RTFHSs were implanted using valveless shunting catheters. No patients developed acute intracranial hemorrhage or new neurological deficit postoperatively. During the follow-up of 17.2 ± 13.7 months (range 3-39 months), all patients showed clinical and radiological improvement. The mean KPS score at the last follow-up was significantly increased to 88.0 ± 10.3 (range 70-100, p<0.0001). RTFHS resulted in significant complete remission in PVBE and midline shift in 8 (80.0%, p=0.0007) and 9 (100.0%, p=0.0001) patients, respectively. As the postoperative follow-up duration prolonged, the mean TTH volume decreased in a consistent, linear trend (p<0.0001). At last follow-up, the mean TTH volume was significantly reduced to 15.4 ± 11.5 cm3 (range 5.6-44.1 cm3, p=0.0003), resulting in a mean relative reduction of 77.2 ± 13.1% compared with the volume of TTH at onset. Over drainage was not observed during the follow-up. No patient suffered from proximal or distal shunt obstruction or shunt related infection, and the revision rate was 0%. Conclusion RTFHS seems to be safe and effective for the treatment of TTH with favorable outcomes. Advantages of this technique could be technically less complex and invasive, cost-effective, avoidance of various intraperitoneal complications, and maintaining a near-physiological CSF pathway.